An interval statistical energy method for high-frequency analysis of uncertain structural–acoustic coupling systems. Issue 12 (1st December 2020) - Dong, J. H.; Ma, F. W.; Hao, Y. D.; Gu, C. S.
Abstract : An interval statistical energy method is proposed to calculate the variation range of high-frequency vibration energy for acoustic–vibration coupling systems with uncertain material parameters. Instead of using statistical energy analysis parameters as the uncertainty variables, material physical parameters, with a clearer physical meaning, are used; this is convenient for determining the perturbation interval and avoiding mutual coupling among the uncertain parameters. In this novel method, the derivative matrix of the loss factor matrix with respect to material parameters is derived, and the sensitivity during the uncertain transfer process is obtained analytically. This approach is more accurate than previous numerical methods. Using this interval statistical energy method, numerical examples are calculated and compared with results obtained using the Monte Carlo method, which shows that this method can effectively and accurately calculate the variation range of the system vibration energy under the condition of material uncertainty for structural–acoustic coupling systems.